(untitled)
The forager-exploiter model with gradient-dependent flux-limitation u_t=Δ u-χ abla · (uk_f(1+| abla w|^2)^-α2 ) abla w,v_t=Δ v-ξ abla · (vk_g(1+| abla u|^2)^-β2 ) abla u,w_t=Δ w-(u+v)w-μ w+r(x,t)is considered in smooth bounded domains Ω ⊂ R^N, N ≥ 2. It is shown that if α > (N − 2)/N(N − 1), β > 0, then for any nonnegative functions u_0, v_0, w_0∈ W^2,∞(Ω) such that u_0 ot0 and v_0 ot0, the problem has a global classical solution (u, v, w) ∈ (C^0 (Ω × [0,∞))C^2,1(Ω × (0,∞)))^3. , number=4, journal=East Asian Journal on Applied Mathematics, year=2022, month=Aug., pages=848–873